De la libération des enfants à la violence des pédophiles. La sexualité des mineurs dans les discours politiques des années 1970 - Jean Bérard (Genre, Sexualité et Société)
Since the 1980s, paedophilia has been a socially reproved deviant sexual behaviour which constitutes a criminal offence. That description partly masks the nature of 1970s debates on the age of consent. The rebellion of young people against parental power and the will to eliminate legal infringements on sexual freedom have made a strong impression on the first few years after may 1968. After 1975, the decline of these movements left a space for the demands of adults wishing to practice their sexuality with children. Their demand became a controversial topic in the context of the struggle for the depenalization of homosexual sex with minors. However, these claims have been marginalized and silenced at the beginning of the 1980s due to the compromise made with the new socialist government.